Upaya Mewujudkan Karakter Peserta Didik Yang Berakhlak Mulia - Faisal; Norwinda (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
The word "character" originates from the Greek language meaning "to mark," which refers to the process of implanting good values into a person's behavior. Character education aims to improve the quality of the learning process by emphasizing the comprehensive and balanced strengthening of character and noble morals. This research aims to describe various efforts that can be made to realize students' noble moral character based on a literature review. The research was conducted using a qualitative method with a literature study approach. Data was collected from various written sources, such as journals and articles related to the research topic. The results show that various efforts can be made to realize a noble moral character, such as the exemplary behavior of parents and teachers, strengthening religious activities, habitual worship, effective student management, and optimizing the role of Islamic boarding schools or religious-based schools. Teachers hold a central position as educators and role models who influence moral development through their pedagogical, personal, social, and professional competencies. Overall, the formation of noble morals can only be realized through a holistic approach that consistently involves all parties. With effective synergy and a positive environment, students can grow into a generation of character, refinement, and noble morals, in accordance with Islamic values. Keywords: Character Education, Students, Exemplary Character/Morals. Abstrak Kata "karakter" berasal dari bahasa Yunani yang berarti "to mark" atau "menandai", yang merujuk pada proses menanamkan nilai-nilai baik dalam perilaku seseorang. Pendidikan karakter bertujuan untuk meningkatkan kualitas proses pembelajaran dengan menekankan penguatan karakter dan akhlak mulia secara komprehensif dan seimbang. Penelitian ini bertujuan untuk mendeskripsikan berbagai upaya yang dapat dilakukan untuk mewujudkan karakter peserta didik yang berakhlak mulia berdasarkan hasil kajian literatur. Penelitian ini dilakukan dengan metode kualitatif menggunakan pendekatan studi kepustakaan. Data dikumpulkan dari berbagai sumber tertulis, seperti jurnal dan artikel yang berkaitan dengan topik penelitian. Hasil penelitian menjukkan bahwa berbagai upaya dapat dilakukan untuk mewujudkan karakter yang berakhlak mulia, seperti keteladanan orang tua dan guru, penguatan kegiatan keagamaan, pembiasaan ibadah, pengelolaan kesiswaan yang baik, serta optimalisasi peran lembaga pesantren atau sekolah bercorak keagamaan. Guru memiliki posisi sentral sebagai pendidik dan teladan yang memengaruhi perkembangan akhlak melalui kompetensi pedagogik, kepribadian, sosial, maupun profesional.  Secara keseluruhan, pembentukan akhlak mulia hanya dapat terwujud melalui pendekatan holistik yang melibatkan seluruh pihak secara konsisten. Dengan sinergi yang efektif dan dukungan lingkungan yang positif, peserta didik dapat tumbuh menjadi generasi berkarakter, beradab, dan berakhlak mulia sesuai nilai-nilai Islam. Kata kunci: Pendidikan Karakter, Peserta Didik, Akhlak Mulia.